Removing Ovarian Tumours Vaginally:The Odyssey of a Gynaecologist (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: benign ovarian tumours; vaginal hystere- ctomy; vaginal removal of benign ovarian tumours; veress needle